Psychological characteristics of healthy lifestyle and self compassion in socially active elderly persons - Kapustina V.A.; Melnikova A.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the relationship between the components of a healthy lifestyle and self-compassion in socially active elderly people. Methods and structure of the study. To achieve the goal, tools were used - psychodiagnostic testing using the questionnaire «Profile of a Healthy Lifestyle» by M.D. Petrash, O.Yu. Strizhitskaya, I.R. Murtazina, self-compassion scales by K. Neff, adaptation by K.A. Chistopolskaya, E.N. Osina, S.N. Enikolopova. The study involved 86 respondents aged 57 to 79 years. Testing was carried out on the basis of the Novosibirsk State Technical University. Results and conclusions. An average level of self-compassion was revealed in socially active older women and a high expression of most components of a healthy lifestyle. Correlation analysis using Spearman’s Rs test showed the presence of significant connections between the components of a healthy lifestyle and the parameters of self-compassion, in particular, correlations were found between mindfulness, self-kindness, and over-identification with such components of a healthy lifestyle as internal growth and stress management. Socially active older women who show a balanced, friendly and attentive attitude to their experiences at a high level have high rates of desire for self-realization and the ability to recognize and counteract sources of stress. The results of the study suggest that incorporating psychological and self-compassion techniques can improve healthy lifestyles, increase resilience to stress, and promote healthy aging.